Subdesarrollo, actitud petitoria y cambio social - Polo, Leonardo (Mercurio Peruano, 2020)
Poor organization of work and the low performance that it generates is in the root of underdevelopment, and it is therefore stated that education is the only possibility of breaking the obstacles that prevent a real transformation. The investment in education must be completed by the support of foreign universities that generate knowledge as engines of change across the improvement of their cultural standards. Opposite to this, it is necessary to avoid the danger that encloses the “implorian attitude” that carries in advance a resignation to the possibility that a country could take charge of its own matters.